Moralities of juvenile shrimp, Penaeus monodon, associated with Penaeus monodon baculovirus, cytoplasmic reo-like virus, and rickettsial and bacterial infections, from Malaysian brackishwater ponds - Anderson, I. G.; Mohamed Din, Mohamed Shariff; Nash, G.; Nash, Marilyn (Asian Fisheries Society, 1987)
A disease syndrome from Malaysia in extensively reared Penaeus monodon, in which P. monodon baculovirus (MBV), a cytoplasmic reo-like virus, rickettsia and bacteria were identified pathologically, is described. Typical MBV lesions were apparent in hepatopancreas; the reo-like virus did not produce any light microscope-visible lesions. Rickettsial microcolonies, present in hypertrophied connective tissue cells throughout all shrimp tissues, were associated with hemocyte infiltrations, aggregations and granulomas with melanization and fibrocytes. The organs with the highest prevalence of rickettsia-associated lesions were the heart, hepatopancreas, Y-organ, gills and parietal hemocoele linings. The Gram-negative, rod-shaped bacteria were associated with tissue changes and had a tissue distribution typical of a penaeid bacterial septicemia. Histologically, the rickettsia appeared primarily responsible for the disease with the secondary bacterial infections contributing to the mortalities seen. MBV and the reo-like virus may have facilitated the rickettsial infection or may have become patent in the weakened shrimp.